Behavior of steel-concrete-steel sandwich beams with blot connectors under off-center impact load. (November 2021) - Wang, Yonghui; Sah, Tilak Prasad; Lu, Jingyi; Zhai, Ximei
Abstract: The structural performance of the Steel-Concrete-Steel (SCS) sandwich beams with bolt connectors subjected to off-center impact load was investigated in this paper. Nine SCS sandwich beams were tested under impact loading by employing a drop hammer impact test system. The influences of concrete core depth, steel plate thickenss, top to bottom steel plate thickness ratio, and impact location on the responses of SCS sandwich beams were experimentally studied. The experiments revealed three failure modes of the SCS sandwich beams, i.e., flexure, flexure-shear, and fracture of the bottom steel plate. The separation of steel plates was prevented, and the structural integrity of the SCS sandwich beams was maintained despite the impact near the support, owing to the presence of bolt connectors. An analytical model was developed to predict the displacement–time histories of the SCS sandwich beams subjected to impact load. The predicted displacement responses showed a good match with the experimental results. Moreover, the force–displacement curves obtained from the analytical model and impact tests were compared, and good agreement between them could be observed. Graphical abstract: Unlabelled Image Highlights: Off-center impact behaviors of SCS sandwich beams with bolt connectors were investigated. Three failure modes, i.e., flexure, flexure-shear and fracture of bottom plate for the SCS beams. The locations of impact on the SCS sandwich beams changed their failure modes. An analytical model was proposed for predicting impact-induced displacement of the SCS beam.